(untitled) (Revista Iberoamericana de Bioética, 2020)
The UN’s Sustainable Development Goal 11 proposes transforming cities to make them inclusive, safe, resilient and sustainable. The article is a critical analysis from an urban bioethics approach. Before achieving this goal, first a discussion is required about the model of development behind it. In response to the chaotic situation of the cities, two models are proposed: Smart Cities and Sustainable Cities, but their effectiveness depends of a basic question, often ignored, relating to the economic paradigm that supports the proposal. The situation of big cities reveals the vulnerability of their population and the need for socioenvironmental resilience and sustainability based on an integral ecology.